Polyphenols, aging, and health: What can we expect from the food industry in the technology era? - Numa, Iramaia Angelica Neri; Sancho, Renata Aparecida Soriano; Wolf, Kendji Eduardo; da Silva Miranda, Cynthia Tereza Corrêa; Soares, Stephanie Dias; de Souza Lima, Adriana; Pastore, Glaucia Maria (Frontiers in Medicine, 2025)
BackgroundAging is a physiological process characterized by several metabolic changes, oxidative stress and inflammatory processes accumulated throughout life, reflecting in several diseases. Adopting a healthy lifestyle, including a diet rich in polyphenols, can play a crucial role in promoting healthy aging, since these compounds are capable of regulating several signaling pathways as well as modulating the intestinal microbiota and being involved in epigenetic modifications. With the advancement of technology and omics sciences, the food industry is undergoing a rapid transformation toward personalizing and customizing nutritional solutions that consider each individual’s health conditions, preferences, and lifestyles. Therefore, such niche that will become predominant worldwide.Scope and approachThe scope of this review focuses on the role of polyphenols in diseases related to aging, providing an overview of alternatives for personalized nutritional plans, including the role of the food industry in the technological era to meet the unique needs and to develop new food products for the elderly population.Key findings and conclusionFood products for older people represent opportunities in a niche that will become predominant worldwide. In this sense new technologies offers new possibilities for innovation in the food industry production chain that aim to improve not only the nutritional characteristics of foods but also improvements in food processing, food safety, and quality assurance.